Enhancing Cardiovascular Disease Risk Prediction: A Comparative Analysis of Machine Learning Techniques - Eldesouky, Esraa; Elashmawi, Walaa H.; Salama, Ahmed S.; Ali, Ahmed; Mahfouz, Magi (Journal of Computational and Cognitive Engineering, 2026)
Cardiovascular disease (CVD) remains a global health threat. Accurately assessing CVD risk is crucial for preventative measures and interventions. This paper explores advancements in CVD risk prediction by examining several approaches and trials designed with the aim of diagnosing myocardial infarction (MI), which is generally known as a heart attack. MI is a critical medical condition in which a blocked artery cuts off blood flow and oxygen to a specific part of the heart muscle. This starves the heart tissue, leading to permanent damage and ranking as a top cause of mortality globally. By analyzing vast amounts of patient data, machine learning (ML) algorithms can predict the probability of a heart attack, pinpointing high-risk individuals. This allows for preventative measures and early intervention. The study in this paper utilizes tabular data for risk factors and includes an examination of multiple ML models to improve diagnostics, particularly for high-risk MI. These ML models include random forest classifiers, decision tree classifiers, support vector machines, logistic regression, and gradient boosting (GB). The experimental results reveal that GB has achieved higher accuracy than other models. This provides insights into enhancing cardiovascular health monitoring and diagnosis in clinical settings. Received: 8 July 2025 | Revised: 15 December 2025 | Accepted: 5 March 2026 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement The data that support the findings of this study are openly available in Kaggle at https://www.kaggle.com/datasets/ritwikb3/heart-disease-cleveland. Author Contribution Statement Esraa Eldesouky: Conceptualization, Project administration, Funding acquisition. Walaa H. Elashmawi: Conceptualization, Software, Formal analysis, Resources, Supervision. Ahmed S. Salama: Data curation, Writing – review & editing. Ahmed Ali: Methodology, Investigation, Writing – original draft. Magi Mahfouz: Validation, Visualization.